ANALISIS DAN PERANCANGAN USER INTERFACE PADA APLIKASI REPARATION MENGGUNAKAN METODE GOAL DIRECTED DESIGN - Ruslim, Henderson; Munir, Abdul; Surasa, Hendra (STMIK KHARISMA Makassar, 2024)
This research aims to redesign the user interface of the Reparation application, a motorcycle repair service in Makassar, using the Goal-Directed Design (GDD) method. Data collection was carried out through interviews and questionnaires with 20 users, and the data was processed using the System Usability Scale (SUS). The initial test obtained an average SUS score of 46.375 with a